Quadriláteros inscritíveis e os teoremas de Simson-Wallace e de Steiner-Lehmus - Lago, Rodrigo Cesar (2018)
We present in this work different strategies to demonstrate Simson-Wallace and Steiner-Lehmus theorems, the latter not approached in references of geometry used in PROFMAT and with rare approaches in geometry books in Portuguese. We emphasize in the demonstrations the properties of inscribed quadrilaterals and we discuss about direct proofs and proofs by contradiction of Steiner-Lehmus theorem. We also suggest investigative activities for mathematics teachers in Elementary and High School. In these activities, we explore the demonstration of SimsonWallace and Steiner-Lehmus theorems using GeoGebra, a free software of dynamic geometry.